Governance mechanisms and audit fees in Islamic banking institutions in Malaysia - Ahmad, Maslina; Annuar, Hairul Azlan; Vendy, Vicky (2019)
The purpose of this study is to examine whether corporate governance mechanisms affect the audit process in terms of audit fees in Islamic banking institutions in Malaysia. The governance mechanisms are the characteristics of board of directors (size and independence), the characteristics of audit committee (size, expertise, independence and meetings) and the characteristics of shariah committee (size and expertise). The annual reports of 16 Islamic banks in Malaysia for seven years (2011-2017) were examined. From panel data regression using 112 observations of the study sample, this study finds that audit committee independence and shariah committee expertise have significant association with audit fees. This study provides support for the step up practice recommended in MCCG 2017 regarding the importance of establishing audit committee that comprises solely independent directors. It also suggested that the shariah committee with accounting qualification/background could ensure not only the shariah-compliance of Islamic banking and finance business but also decrease the external audit fees.